2014
DOI: 10.1371/journal.pone.0108136
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Perceived Insecurity from Crime in Adults: A Population-Based Study

Abstract: BackgroundThe present study aimed to describe the perception of safety from crime in the neighborhood and to evaluate its association with leisure-time and transport-related physical activity in adults.MethodsA cross-sectional population based study was conducted in the urban area of Pelotas, Brazil, in 2012. Perceived insecurity from crime in the neighborhood was measured using the Neighborhood Environment Walkability Scale (NEWS) and the City Stress Inventory (CSI). Physical activity was measured using an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Regarding the results, eight studies found an association 12,13,16,18,19,21,22,26 between perception of safety and PA practice, all indicating a direct association. Nonetheless, five studies did not show an association between these variables 17,20,[23][24][25] . Perception of safety varied among the following: overall perception of safety 12,13,19,[20][21][22]25 , safety against crimes 23,24 , fear of staying at home or leaving home during the day or night 16,17 , traffic safety 18 and safety against crimes and in traffic 26 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Regarding the results, eight studies found an association 12,13,16,18,19,21,22,26 between perception of safety and PA practice, all indicating a direct association. Nonetheless, five studies did not show an association between these variables 17,20,[23][24][25] . Perception of safety varied among the following: overall perception of safety 12,13,19,[20][21][22]25 , safety against crimes 23,24 , fear of staying at home or leaving home during the day or night 16,17 , traffic safety 18 and safety against crimes and in traffic 26 .…”
Section: Resultsmentioning
confidence: 92%
“…With regard to the scale of quality of articles, the mean scores achieved in the present review study was 14.1 ± 1.0, thus showing good quality. Of all 17 points possible, certain studies 13,19,[24][25][26] achieved a higher score (15 points) and the study by Roman et al 23 obtained the lowest score, 12 points. The score of each item and the total score obtained in each study are shown on Table 1.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The variables representing these items were different in 2015 and in 2012, but the loss of effect may be following the changes related to gender. Some studies indicate gender specificities as related to these variables' trend, although they move in opposite directions, since physical activity has been described as less prevalent among girls than among boys [23][24][25] , and part-taking in social networks and groups of friends became more expressive 25 .…”
Section: Discussionmentioning
confidence: 99%
“…21 Estudos mostram que características do bairro de residência, como disponibilidade de transporte público, segurança no tráfego, infraestrutura para uso de bicicleta, disponibilidade de equipamentos públicos recreacionais, e mesmo a presença de áreas verdes, proporcionam maior prática de atividade física 22,23 , já a criminalidade e a insegurança são fatores que a influenciam negativamente. 24,25 Resultados obtidos a partir de populações idosas também apontam associações entre aspectos contextuais e desfechos de saúde. [26][27][28][29][30][31][32] Por exemplo, idosos que residem em regiões com maior desigualdade de renda, medida pelo índice de Gini, apresentam maior chance de relatarem pior estado de saúde.…”
Section: Determinantes Sociais E O Envelhecimentounclassified